PERFORMA PERTUMBUHAN ROTIFERA (Brachionus rotundiformis) MELALUI PEMBERIAN FERMENTASI IKAN TONGKOL DAN RAGI ROTI - Anima, Ridayus; Hendri, Afrizal; Saputra, Fazril; Diansyah, Sufal; Fadhillah, Radhi (Universitas Teuku Umar, 2022)
Natural feed is one of the inputs that is needed during the rearing phase of fish larvae, especially when the york content has been completely absorbed by the fish's body. There are many types of natural food commonly used by marine fish hatcheries, both phytoplankton and zooplankton. Rotifera (Brachionus rotundiformis) is one of the zooplankton that can be used as natural food for fish larvae. This study aims to determine the effect of fermented tuna and rag roti on the growth performance of rotifers. This research was conducted in November - December 2021 at the Fish Seed Center (BBIP) Busung Indah, Simeulue Regency. The study was conducted experimentally using a completely randomized design (RAL) with four treatment levels and three repetitions. The results showed that different fermented tuna and baker's yeast on culture media had a significant effect on population density and growth rate of Rotifera significantly (P<0.05). Treatment (P4) 8 g of fermented fish added yeast 0.60 g was significantly different from the control treatment (P0), treatment (P1), treatment (P2), but not significantly different from the treatment (P3) tuna 8 g added bread yeast 0.45 g. The results of this study showed that the administration of fermented tuna and baker's yeast at a dose of 8 g and baker's yeast 0.60 g had a positive impact on the growth performance of rotifers, with an average of 196 ind/mL/day.